Executive leadership, policy tourism, and policy diffusion among local governments. (7th July 2022) - Yi, Hongtao; Liu, Ivy
Abstract: Policy tourism is an important but rarely studied phenomenon describing a widespread practice, through which local public and business leaders form delegations, choose target cities, and implement intercity policy diffusion, business exchange, and economic collaboration. Our research examines how executive leadership characteristics, city‐level contextual factors, and interdependence mechanisms relate to cities' decisions to visit. Using two‐stage probit selection models with instrumental variables on a dyadic balanced panel dataset recording all policy tourism events between major U.S. cities from 2007 to 2016, we answer this question accounting for potential endogeneity problems. Our findings suggest that cities with experienced yet newly appointed, minority leaders tend to visit cities with experienced white or female leaders. Additionally, policy tourism happens among cities embedded in highly complex, munificent, and turbulent environments. Finally, cities tend to learn from peers with higher economic prosperity or interact with their competitors.